Answer:
wheres the reszt of the question?
Step-by-step explanation:
Answer:
3
Step-by-step explanation:
We know x = -2, so we can substitute -2 in for x
3x^2- 9
3*-2^2-9
Solve the exponent first (PEMDAS)
3*4-9
Multiply next
12-9
Subtract
3
I’m sorry if I’m wrong but the equation be 3x+6=2x and if you solve that, x=6.
Explanation: 3x+6=2x
-3x. -3x
6=x
Answer:
30+4+0.7+0.05
Step-by-step explanation:
Because the expanded form is added the number.
3=30
4=4.
7=0.7
and 5=0.05 so all together is 30+4+0.7+0.05
This problem boils down to 5/6 - 1/4
To subtract these fractions you need a common denominator.
I'll use 12
The first fraction becomes 10/12 and the second fraction becomes 3/12
10/12-3/12 = 7/12
So Jacob is 7/12 of a foot taller than Linda.
Also note than since 12 inches = 1 foot, you could say Jacob is 7 inches taller than Linda